PENGEMBANGAN BAHAN AJAR UNTUK MENUNJANG PEMBELAJARAN KURIKULUM MERDEKA PADA MATERI BENTUK MOLEKUL FASE F SMA/MA - Farras Aulia Sugria; Mawardi Mawardi; Fajar Isnaeni (Fakultas Keguruan dan Ilmu Pendidikan, Universitas Kristen Indonesia, 2023)
After the pandemic, the Ministry of Culture, Research and Technology issued a solution to overcome learning lag, namely the implementation of an Merdeka Curriculum. In its implementation, the current Merdeka Curriculum still has obstacles regarding the availability of incomplete teaching materials, especially in Phase F chemistry learning. This study aims to develop and determine the level of validity of teaching materials on molecular shapes so that they can support the Merdeka Curriculum in Phase F chemistry learning SMA / MA. Teaching materials were developed based on the Plomp model developed by Tjeerd Plomp. There are 3 stages, namely initial investigation, prototype development, and assessment. Data were collected through primary data derived from the results of interviews, validity, and practicality. The results of individual interviews with students show that teaching materials have attracted the attention of students, the results of validity derived from 5 UNP chemistry lecturers obtained a score v = 0.82 with a valid category, while the results of practicality derived from 2 teachers of SMAN 2 Padang obtained a score NP = 88% and and 9 students obtained a score NP = 95% so that both are categorized as very practical. Based on this, this teaching material is suitable for use to support the Merdeka Curriculum. Teaching materials are expected to be a solution for teachers in carrying out chemistry learning in accordance with the Merdeka Curriculum to create students who have critical thinking, careness and complex problem solving skills.